2022
DOI: 10.1002/tee.23646
|View full text |Cite
|
Sign up to set email alerts
|

Human–Machine Interfaces Based on Bioelectric Signals: A Narrative Review with a Novel System Proposal

Abstract: Bioelectric signals such as electromyogram (EMG) and electroencephalogram (EEG) reflect human internal states and intended actions, and have therefore been applied to various types of human-machine interfaces. Such biosignal-based interfaces are beneficial because they not only allow intuitive control of machines, but can also support persons with disabilities. In this paper, we review the recent studies on human-machine interfaces based on bioelectric signals including EMG and EEG signals. Furthermore, we int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We employed nonnegative matrix factorization (NNMF) algorithm [42] to extract the weighting matrix and the associated activation signals from the sEMG (or force) data matrix according to (1). NNMF is characterized by the nonnegativity of derived solutions, and thereby allowing correct physiological interpretation of the extracted synergies.…”
Section: Synergy Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed nonnegative matrix factorization (NNMF) algorithm [42] to extract the weighting matrix and the associated activation signals from the sEMG (or force) data matrix according to (1). NNMF is characterized by the nonnegativity of derived solutions, and thereby allowing correct physiological interpretation of the extracted synergies.…”
Section: Synergy Extractionmentioning
confidence: 99%
“…As a result, it usually requires a large amount of data and time for these nonlinear models to learn effectively, which may not be a good choice in real-world scenarios where the amputees prefer to control the prosthetic hand with less training time. In addition, synergies have long been regarded as the building blocks of complex motor behaviours, and the concept of muscle/force synergies are essentially based on a linear model given by (1). Over the last few decades, it has been well demonstrated that the linear model of synergies can be implemented mechanically using differential mechanisms to simplify the design and control of robotic hands [33][34][35].…”
Section: Correspondence Between Muscle and Force Synergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The noise typically arises when there is movement in the body while collecting the EEG signal. Eliminating this noise from the signal can be a challenging task because the amplitude of the EEG signal is very low [Hayashi & Tsuji, 2022]. The headsets contain electrodes that capture signals from the brain.…”
Section: Pre-processingmentioning
confidence: 99%
“…EMG is a system that detects the muscles’ electric activity and its nerves’ biosignals [ 52 ]. The detected signals can give an indication of the muscles’ health [ 53 ]. However, in the case of speech recognition, the muscles’ movement can indicate the speech behaviour and its relationship with the tongue muscle motion [ 54 ].…”
Section: Introductionmentioning
confidence: 99%